The Search and Identification of Newtonian Dark Matter - M. Ja. Ivanov (Physics of Entropy, Radiation and Gravitating Matter with Examples of General and Analytical Solutions, 2021)
In the Newtonian method of a gaseous compressible medium, the paper considers Dark Matter (DM). On the compressible medium case, this phenomenologic and kinetic approach is based on Newtonian classic (non-relativistic) concepts and generalised linear and nonlinear Maxwell’s electromagnetic theory. Newtonian Dark Matter (NDM) is non-barionic gaseous type matter that forms galaxy halos and a uniformly distributed background of unobserved matter in the universe. This theoretical recognition allows all big NDM performances to be calculated in a free space (mass value m = 3,4 X 10-4 eV, average velocity of particles, etc.). The complete conservation law frameworks for NDM simulation are obtained using classical hydrodynamic methodology (in Euler and Maxwell notions).Conservation laws lead to linear and nonlinear equation systems, which provide a closed mathematical formulation for NDM dynamic problems. The developed NDM theory allows for demonstration of the universe’s typical properties on macro and micro scales. The study of exact solutions of nonlinear equation systems in the presence of internal electrical and gravity force fields is presented in this paper. The final section of the paper addresses the NDM search possibilitiesand explanation of some having experimental data. A few special experimental tests for direct NDM detection are observed.